UNNECESSARY AND HARMFUL MEDICATION USE IN COMMUNITY DWELLING PERSONS WITH DEMENTIA. (20th December 2022) - Deardorff, W James; Jing, Bocheng; Growdon, Matthew; Yaffe, Kristine; Boockvar, Kenneth; Steinman, Michael
Abstract: Persons with dementia (PWD) often have multiple comorbidities which results in extensive medication use despite potentially limited benefit and increased risk of adverse events. Compared to the nursing home, little is known about medication overuse and misuse among the 70% of PWD in the community. Therefore, we examined medication use from Medicare Part D prescriptions among 1, 289 community-dwelling PWD aged ≥66 from the Health and Retirement Study. We classified medication overuse as over-aggressive treatment of chronic conditions (e.g., insulin/sulfonylurea use with hemoglobin A1c<7.5%) and medications inappropriate near the end of life. We classified medication misuse as medications that negatively affect cognition (strongly anticholinergics/sedative-hypnotics) and problematic medications (using Beers and STOPP criteria). We describe the prevalence and patterns of different types of medication overuse/misuse. Frequently problematic medications included antipsychotics (9%), benzodiazepines (12%), and gabapentinoids (13%). Our findings highlight the burden of unnecessary/harmful medications among PWD and inform future deprescribing interventions.